(untitled) (Research, Society and Development, 2022)
The Primary Health Care (PHC) is represented through essential and derived attributes. The monitoring frequently is essential to ensure a good result for health. The PCATool is a validated instrument that ensures the evaluation of PHC based on the structure and process of the performance analyzing the essential and derived attributes. This scope review aims to map the studies that evaluated the quality of oral health actions and services in PHC through the PCATool instrument. The research question was based on the PCC (Population, concept, and context) strategy and followed the PRISMA-ScR recommendations. All included studies used the PCATool assessment instrument to assess the quality of oral health services offered in PHC, without restriction to the year and language of publication. Four studies were selected, that answer all the inclusion criteria and the information were analyzed. All studies found evaluated the quality of oral health in PHC based on the essential attributes and derived from the PCATool, in total, data from 2848 participants were detected. Most studies found a high quality of PHC, which proves the improvement of the public oral health service in Brazil, although many users find it difficult to access oral health services. This scoping review found few studies that used the PCATool as an assessment tool in oral health services. Therefore, it is recommended that more research use the tool and its versions for a consistent evaluation.